Management of Hypertension in Pregnancy - Nurike S Mudjari; Nur Samsu (Acta Medica Indonesiana)
Hypertension-related maternal mortality reaches 16% when it is compared to other causes of maternal mortality such as sepsis, bleeding or abortus. Pregnant women with hypertension disorder are at increased risk for experiencing numerous complications including disseminated intravascular coagulation (DIC), cerebral hemorrhage, liver dysfunction and acute renal failure; while to the fetus, it may cause intrauterine growth retardation, prematurity and perinatal mortality. Hypertension in pregnancy should be managed appropriately to reduce maternal and fetal morbidity and mortality rate, i.e. by preventing women from getting the risks of increased blood pressure, preventing disease progression and preventing the development of seizure and considering termination of pregnancy in lifethreatening situation for maternal and fetal health.